On the Fine Spectra of the Generalized Forward Difference Operator ∆v Over the Sequence Space ℓ1: Javad Fathi, Rahmatollah Lashkaripour - Team, Support (Thai Journal of Mathematics, 2011)
The main purpose of this paper is to determine the fine spectrum of the forward difference operator over the sequence space ℓ1.